Energy Management System for Hybrid Renewable Energy-Based Electric Vehicle Charging Station - Karmaker, Ashish Kumar; Hossain, Md Alamgir; Pota, Hemanshu Roy; Onen, Ahmet; Jung, Jaesung (IEEE Access, 2023)
This paper introduces an energy management algorithm for a hybrid solar and biogas-based electric vehicle charging station (EVCS) that considers techno-economic and environmental factors. The proposed algorithm is designed for a 20-kW EVCS and uses a fuzzy inference system in MATLAB SIMULINK to manage power generation, EV power demand, charging periods, and existing charging rates to optimize real-time charging costs and renewable energy utilization. The results show that the proposed algorithm reduces energy costs by 74.67% compared to existing flat rate tariffs and offers lower charging costs for weekdays and weekends. The integration of hybrid renewables also results in a significant reduction in greenhouse gas emissions, with payback periods for charging station owners being relatively short, making the project profitable.
Keywords: Charging station; Economic factors; Electric vehicle charging; Electric vehicle charging station; Energy management algorithms; Energy-based; Fuzzy-Logic; Hybrid renewable energies; Renewable resource; Techno-economics; Electric vehicle; electric vehicle charging station; fuzzy logic; renewable resources